1A.07: GENOME-WIDE PROFILING OF LONG NONCODING RNA EXPRESSION PATTERNS IN THORACIC AORTA FROM SPONTANEOUSLY HYPERTENSIVE RATS. (June 2015) - Yu, J.; Cai, Y.; Liu, Y.; Yang, Y.; Chen, Y.; Jose, P.A.; Wang, D.; Zhou, L.; Zeng, C.
Abstract : Objective: Numerous studies have indicated that long non-coding RNAs (lncRNAs) are involved in the cardiovascular development, as well as pathology, such as heart failure and coronary arterial disease. However, the roles of lncRNAs in essential hypertension remain unclear. Here we investigated the genome-wide lncRNA expression profiles in the aorta of spontaneously hypertensive rats (SHR), a rodent model of essential hypertension. Design and method: LncRNA and mRNA expression profile were analyzed with GeneChip® Rat Gene 2.0 ST Array. Quantitative real-time PCR was used to validate 9 candidate lncRNAs. Bioinformatics analysis including Gene Ontology (GO) analysis, pathway analysis, and lncRNA-mRNA co-expression network analysis were carried out for further investigation. Results: Microarray data showed that 29 lncRNAs as well as 1159 mRNAs, were differentially expressed. GO analysis showed that "ion transport" were most significant in both up- and down-regulated genes. Pathway analysis indicated that "metabolic pathway" may be especially important in the pathogenesis of hypertension. Conclusions: These findings revealed differentially expressed lncRNAs in the artery of SHR, which may provide novel insight into the roles of lncRNAs in the pathogenesis of essential hypertension.